A synopsis of the pin-hole borers of Thailand (Coleoptera: Curculionidae: Platypodinae) - Beaver, R. A.; Liu, L-Y. (Zootaxa, 2013)
The present state of knowledge of the pin-hole borers of Thailand is summarised to provide a basis for future studies of the fauna and its economic importance in forestry and timber production. A checklist of the fauna is provided with infor-mation on local and world distribution, host trees, biology and taxonomy. Six faunal elements based on geographical dis-tribution, and the host preferences of species are discussed. Ninety-two species have now been recorded in Thailand, of which forty-three are recorded here for the first time. Three species are endemic to Thailand. The following new combi-nations are given: Dinoplatypus piniperda (Schedl), Treptoplatypus fulgens (Schedl), both transferred from Platypus.